1998
DOI: 10.1016/s0042-6989(97)00462-8
|View full text |Cite
|
Sign up to set email alerts
|

Frugivory and colour vision in Alouatta seniculus, a trichromatic platyrrhine monkey

Abstract: It is a long-standing hypothesis that primate trichromacy evolved to help fruit-eating primates find fruits amongst leaves. We measured the reflectance spectra of fruits eaten by a trichromatic primate, Alouatta seniculus, in the rainforest of French Guiana, as well as those of the leaves that form the natural background to fruits. We develop a method of specifying these natural colour signals in a chromaticity diagram appropriate for A. seniculus. By treating the task facing frugivorous monkeys as a signal de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
114
1
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(119 citation statements)
references
References 22 publications
0
114
1
2
Order By: Relevance
“…It has long been an article of faith that the detection and discrimination of coloured fruits in a foliage background provides a framework for the evolution of trichromatic colour vision (Allen 1879;Polyak 1957) and recently this idea has been expanded to include the possibility that trichromatic colour vision might also prove advantageous in discriminations between the leaves preferentially selected as food items by some primates (Lucas et al 1998). The fruit selection hypothesis has support from modelling studies that have demonstrated that the middle-and long-wavelength pigments of trichromatic primates are spectrally well positioned for the task of discriminating objects having the re£ectance properties of orange and yellow fruits from foliage backgrounds (Osorio & Vorobyev 1996;Regan et al 1998). These investigations indicated that primate trichromacy can provide a useful tool in the detection and discrimination of fruits and this could well serve as an advantage that reinforces and maintains trichromatic arrangements.…”
Section: (B) Erg Spectral Measurements and Behavioural Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has long been an article of faith that the detection and discrimination of coloured fruits in a foliage background provides a framework for the evolution of trichromatic colour vision (Allen 1879;Polyak 1957) and recently this idea has been expanded to include the possibility that trichromatic colour vision might also prove advantageous in discriminations between the leaves preferentially selected as food items by some primates (Lucas et al 1998). The fruit selection hypothesis has support from modelling studies that have demonstrated that the middle-and long-wavelength pigments of trichromatic primates are spectrally well positioned for the task of discriminating objects having the re£ectance properties of orange and yellow fruits from foliage backgrounds (Osorio & Vorobyev 1996;Regan et al 1998). These investigations indicated that primate trichromacy can provide a useful tool in the detection and discrimination of fruits and this could well serve as an advantage that reinforces and maintains trichromatic arrangements.…”
Section: (B) Erg Spectral Measurements and Behavioural Resultsmentioning
confidence: 99%
“…Colour would seem likely as providing a useful cue in guiding such selective behaviour. On the other hand, although the diet of howler monkeys clearly includes an assortment of fruit (Regan et al 1998), members of this genus are much less consistent fruit eaters than spider and woolly monkeys, being described as either foliovoref rugivores or frugivore^foliovores depending on the season (Kinzey 1997). Signi¢cantly too, howler monkeys have been reported`to feed on more immature fruits than other sympatric primates' (Kinzey 1997, pp.…”
Section: (B) Erg Spectral Measurements and Behavioural Resultsmentioning
confidence: 99%
“…One of the most studied signal/receiver systems in this regard is the color vision of insect pollinators and the flowers with which they interact (Chittka 1996;Chittka 1997;Chittka and Briscoe 2001 The evolutionary history we are trying to untangle is potentially paralleled not only by insects and flowers. Similar scenarios may be proposed, for instance, for primates and fruit; did trichromacy evolve in primates to aid in detecting and selecting ripened fruit (Hunt et al 1998;Mollon 1989;Osorio and Vorobyev 1996;Regan et al 1998;Smith et al 2003), or did fruit color evolve to attract seed dispersers more effectively? Our proposal that the relevant component of variation in throat color should be represented along a line through color space may provide useful insight into many such similar questions concerning the evolution of signals and receivers.…”
Section: Generalmentioning
confidence: 90%
“…As anormalidades congênitas são conhecidas como daltonismo, uma homenagem ao químico inglês John Dalton, que em 1794, descreveu sua anomalia (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) .…”
Section: Histórico Da Visão De Coresunclassified